Penerapan media my gymnastict terhadap hasil belajar kognitif materi roll belakang - Suhestiawan, Basuki; Setiyawan; Herlambang, Tubagus (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
This study aims to see the application of my gymnastics media to the cognitive learning outcomes of back roll material. This study uses quantitative research methods using an experimental approach, the population in this study is class XI students of SMA Negeri 2 Rembang, the sampling technique used is random sampling. Data analysis used normality test, homogeneity test, t test (comparative test). Based on the results of the research and discussion, the results of the application of my gymnastics media showed that there were differences in the cognitive learning outcomes of the back roll material for class XI students of SMA Negeri 2 Rembang in the control class and the experimental class. So it can be said that there is an effect of the application of my gymnastics media on the cognitive learning outcomes of the back roll material of class XI students of SMA Negeri 2 Rembang.